Deficiency in perilipin 5 reduces mitochondrial function and membrane depolarization in mouse hearts. (October 2017) - Andersson, Linda; Drevinge, Christina; Mardani, Ismena; Dalen, Knut T.; Ståhlman, Marcus; Klevstig, Martina; Lundqvist, Annika; Haugen, Fred; Adiels, Martin; Fogelstrand, Per; Asin-Cayuela, Jorge; Hultén, Lillemor Mattsson; et al.
Abstract: Myocardial triglycerides stored in lipid droplets are important in regulating the intracellular delivery of fatty acids for energy generation in mitochondria, for membrane biosynthesis, and as agonists for intracellular signaling. Previously, we showed that deficiency in the lipid droplet protein perilipin 5 (Plin5) markedly reduces triglyceride storage in cardiomyocytes and increases the flux of fatty acids into phospholipids. Here, we investigated whether Plin5 deficiency in cardiomyocytes alters mitochondrial function. We found that Plin5 deficiency reduced mitochondrial oxidative capacity. Furthermore, in mitochondria from Plin5 −/ − hearts, the fatty acyl composition of phospholipids in mitochondrial membranes was altered and mitochondrial membrane depolarization was markedly compromised. These findings suggest that mitochondria isolated from hearts deficient in Plin5, have specific functional defects.